2005
DOI: 10.1103/physrevb.72.134519
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence in a superconducting quantum bit circuit

Abstract: Decoherence in quantum bit circuits is presently a major limitation to their use for quantum computing purposes. We present experiments, inspired from NMR, that characterise decoherence in a particular superconducting quantum bit circuit, the quantronium. We introduce a general framework for the analysis of decoherence, based on the spectral densities of the noise sources coupled to the qubit. Analysis of our measurements within this framework indicates a simple model for the noise sources acting on the qubit.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
842
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(874 citation statements)
references
References 46 publications
30
842
0
2
Order By: Relevance
“…(10)(11), this can be derived by applying the Wiener-Khintchine theorem to the cross correlation function, which this time simply gives R (m) b ′ b ′′ = b 2 (the subscript b ′ b ′′ indicates two interleaved sub-series obtained from the original series b n ), and therefore…”
Section: Cross-psd: White-noise Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…(10)(11), this can be derived by applying the Wiener-Khintchine theorem to the cross correlation function, which this time simply gives R (m) b ′ b ′′ = b 2 (the subscript b ′ b ′′ indicates two interleaved sub-series obtained from the original series b n ), and therefore…”
Section: Cross-psd: White-noise Eliminationmentioning
confidence: 99%
“…Their noise is known to be due to local fluctuators [6][7][8][9] and the spectrum exhibits a 1/f α powerlaw dependence from hertz to tens of megahertz [10][11][12][13][14] . Its dependence on the device geometry 15,16 merits further study.…”
Section: Introductionmentioning
confidence: 99%
“…We should mention, however, that decoherence in some versions of charge qubits, namely quantronium and transmon, has been studied in greater detail [47][48][49]. We have measured the charge qubit energy relaxation in a wide range of the qubit parameters and found that it is caused by quantum noise with approximately linear frequency dependence.…”
Section: Energy Relaxationmentioning
confidence: 99%
“…For this reason, environment-induced decoherence has been and is still a main obstacle to the practical application of superconducting qubits in quantum computation. [2,13,14,15,16] The environment-induced decoherence of superconducting qubits has been extensively studied both theoretically [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] and experimentally [2,8,13,21,25,34,35,36,37,38,39,40] in the absence of ac driving fields (free decay). Quite a few proposals, such as dynamical decoupling, [41,42,43,44,45,46,47,48] decoherence free subspaces, [49,50,51,52] spin echoes, …”
Section: Introductionmentioning
confidence: 99%